Prevalence of needle sticks injury and its associated factors among Health Care Workers in Bahir Dar city Health Centers, Northwest Ethiopia - Legesse, Wendmagegnehu Teju; Anemaw, Worku; Mekonen, Teferi; Nigus, Daniel Mekonnen (International Journal of Infection Control, 2015)
It is important for HCWs to remember that over 20 pathogens have been reportedly transmitted from needle stick injuries. The most serious are the transmission of Hepatitis C virus, Hepatitis B virus and Human immunodeficiency virus. World Health organization report showed that 16,000 HCV, 66,000 HBV & 1000 HIV may have occurred worldwide. Two million needle stick injuries are reported in health care providers every year. This study was institution based cross-sectional study conducted in 10 Bahir Dar City public health centres from June to October 2014. 194 health care workers were selected using cluster followed by systematic random sampling technique. Data has been collected using pre tested self-administered questionnaire. The collected data was entered and analyzed by using SPSS statistical software version 20. Bi-variate logistic regression model was used to assess the association between dependent and independent variables and P-value less than 0.05 was considered statistically significant. Among 194 study participants, 83 (42.8%) participants showed history of needle stick injuries. Needle stick injuries were higher in outpatient departments and emergency unit, 59 (30%) and delivery room 40 (20.6%). The proportion of needle stick injuries were higher among health officers 16/30 (53.3%). The major item cause for needle stick injuries were syringe with needle, 55/83 (66%) and the most injured body part were fingers 58/83 (70.7%). In conclusion, significant proportion of health care workers experienced needle sticks injuries. Therefore, ongoing training and supervision should be given to curb the situation in the study area.